Q. 10 A34.1( 9 Votes )

If <span lang="EN

Answer :

a + b = √5


a = √5 – b


a–b = √3


(√5 – b) – b = √3


2b = √5 - √3


b =


a = √5 – b = √5 – =


ab = × = =


(a + b)2 = a2 + b2 + 2ab


(√5)2 = a2 + b2 + 2 ×


a2 + b2 = 5 – 1 = 4

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

In each of the foWest Bengal Board - Mathematics

If <span lang="ENWest Bengal Board - Mathematics

If we subtract <sWest Bengal Board - Mathematics

Let us write a raWest Bengal Board - Mathematics

Let us rationalizWest Bengal Board - Mathematics

Let us write the West Bengal Board - Mathematics

Let us write whetWest Bengal Board - Mathematics

Let us fill up thWest Bengal Board - Mathematics

Let us divide firWest Bengal Board - Mathematics

The product of <sWest Bengal Board - Mathematics